TRAINING NEEDS OF PUBLIC JUNIOR HIGH SCHOOL TEACHERS: AN INPUT FOR A PROPOSED CAPABILITY ENHANCEMENT PROGRAM - Kevin Kertz F. Peñaflor (Galaxy International Interdisciplinary Research Journal, 2023)
Training is very important in any organization that aims at progressing. It plays important roles in the effectiveness of an organization and its workforce. In the Division of Province of Cavite, the result of National Achievement Test for the past three years has not reached yet the target mean percentage score of 75. It is in this regard that the researcher intended to ascertain the training needs of public junior high school teachers in the Division of Province of Cavite. The study made use of descriptive research design. The researcher utilized convenient sampling technique in selecting the 100 participants of the study. This study was conducted using the survey tool adapted from Department of Education Region X, Division of Cagayan De Oro City. The results revealed that the most needed trainings of public Junior High School teachers are on knowledge management, moral transformation, conducting qualitative research, oral communication, enhancing analytical and critical thinking, spread sheets/ data base, and spirituality. The results provide an input for a proposed capability enhancement program for teachers.